Differential games with independent motions - Petrosjan, L. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. А. Петросян. Дифференциальные игры с независимыми движениями L. Petrosianas. Persekiojimo lošimai su nepriklausomais judesiais